Prevention of HIV/AIDS in Indonesian Navy views of Knowledge, Attitude, and Practice - Wirahayu, Arwinda Yuhan; Satyabakti, Prijono (Jurnal Berkala Epidemiologi, 2014)
ABSTRACTHIV/AIDS is a disease that is spreading rapidly in many countries, including in Indonesia. HIV/AIDS can affect anyone regardless of social status, race, religion, gender and age groups, including in Indonesian Navy personnel and their families. This study to identify the prevention of HIV/AIDS views of knowledge, attitudes and practice. The methods used in this research was descriptive observasional with the entire population in Indonesian Navy (Study at Satuan Kapal Eskorta Komando Armada RI Kawasan Timur). Sample size was 87 respondents were selected by purposive sampling technique. Variables in this reaserch are respondent characteristics (age, education, marital status, years of work, mobility), and the prevention of HIV/AIDS from their knowledge, attitude, and practice. The results showed that the characteristics of the respondents most of comprised of age group 20â26 years (54.02%). Most respondents were graduate from high school (87.36%). Most respondents were single (52.87%). Most of respondents were working > 5 years (52.87%) and most of respondents mobility > 5 months (41%). The result of prevention HIV/AIDS showed most of respondents knowledge about HIV/AIDS were in good category (60.91%), most of respondents attitudes about HIV/AIDS were in good category (72.41%). And most of respondents practice about HIV/AIDS were in good category (93.10%). It could be conculed that prevention of HIV/AIDS on Indonesian Navy (Study at Satuan Kapal Eskorta Komando Armada RI Kawasan Timur) are seen from their knowledge, attitudes and practice are in good category. To prevent of HIV/AIDS disease Institution of Indonesian Navy have to always give education or information to all of Indonesian Navy and their family.Keywords: prevention, HIV/AIDS, Indonesian Navy, knowledge, atitude, Â Â Â Â Â Â Â Â Â Â Â Â Â practice